Rum runners - Nelson, William (Motion picture producer and director); Bright, Yves; Boyd, Brian Stuart; Wells, Vernon, 1945-; Into Deep Productions (Firm); Leomark Studios (Firm) ([Valley, Wash.] : ITD Productions, 2016)
Rum Runners is the epic story of two best friends, Vic Hanson and Don Calyer. They get caught running illegal booze across the Canadian border. This outstanding screenplay is inspired by actual events. --
Originally released as a motion picture in 2016
Yves Bright, Brian Stuart Boyd, Kerry Wallum, Billy St. John, Mitch Manina, Crystal Victoria Bell, Vernon Wells.
Cinematographers, Mitch Manina, Bryan Martin, Yves Bright ; editor, Brian Corder ; music, Jeffrey Hayat.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 2, 2018)
Keywords: Smuggling -- Drama; Prohibition -- Drama; Distilling, Illicit -- Drama; Feature films; Internet videos; Streaming video